Effectiveness of the Student Success Course on Persistence, Retention, Academic Achievement, and Student Engagement. Issue 2 (1st February 2017) - Kimbark, Kris; Peters, Michelle L.; Richardson, Tim
ABSTRACT: Despite a great increase in the numbers of students enrolling in higher education, specifically at community colleges, the successful completion rates for these students has remained static since the 1970s. When reviewing strategies to increase student retention and successful completion, the Student Success Course (SSC) has emerged as a promising and prominent strategy for community colleges. Given that, the purpose of this sequential mixed methods study was to determine if participation in a SSC influences persistence, retention, academic achievement, and student engagement on a community college campus. Data were collected from a purposeful sample of 197 SSC participants at a middle sized community college in southeast Texas and compared to a matched sample of 235 non-SSC participants. Twelve former SSC participants were also interviewed in an attempt to build a more empirical understanding of the impact of the SSC on student engagement and, thus, the students' decisions to remain in college. Results of this study indicate that a relationship exists between participation in the SSC and persistence, retention, academic achievement in English and mathematics, and student engagement. Additionally, participants claim that taking the SSC not only altered their perceptions of the importance of the course, but their social and study skills as well.